Oxidation-induced phase transformations of hybrid tin bromide single crystals enable the occurrence of second-harmonic generation. Issue 2 (1st December 2022) - Yu, Binyin; Yang, Can; Song, Zhexin; Liu, Guokui; Wei, Jing; Wu, Qi; Dang, Yangyang
Abstract : Oxidation-induced phase transformations of tin-bromide hybrid single crystals enable the occurrence of second harmonic generation. Abstract : Phase transformations of tin halide hybrid materials play an important role in the formation of structural diversity and optoelectronic versatility due to the oxidability and instability from Sn 2+ to Sn 4+ . Here, we demonstrate the synthesis, growth, phase transformations and fundamental properties of DMESnBr m (DME 2+ = N, N ′-dimethylethylenediaminium; m = 4 or 6) and TMDPSn n Br6 (TMDP 2+ = 4, 4′-trimethylenedipyridinium; n = 1 or 2) single crystals. Interestingly, both DMESnBr4 and TMDPSn2 Br6 single crystals undergo irreversible dissolution–recrystallization-induced phase transformations from Sn 2+ to Sn 4+ in the HBr–H3 PO2 mixed solution when exposed to ambient atmosphere, which easily results in the formation of DMESnBr6 and TMDPSnBr6 . In particular, DMESnBr6 crystallizes in the non-centrosymmetric space group P 21 (no. 4) by single-crystal X-ray diffraction and piezoelectric measurements. The second harmonic generation (SHG) response of DMESnBr6 is about 0.5 times that of potassium dihydrogen phosphate (KDP) with type-I phase matching behaviors. Structural and theoretical analyses show that the SHG effect is attributed to the asymmetrical displacement of SnBr6 octahedra. The oxidation-induced phase transformation behaviors provide new insights into the design and acquisition of novel Sn-based hybrid optoelectronic materials.